Beyond the checklist: understanding rural health vulnerability in a South African context - Richard Vergunst; Leslie Swartz; Gubela Mji; Janis Kritzinger; Stine Hellum Braathen (Taylor & Francis Group, 2016)
Background: Vulnerability in the past has sometimes been measured and understood in terms of checklists or common understanding. It is argued here that vulnerability is a more complex issue than this. Although checklists of vulnerable groups are important, they do not capture the essence and dynamics of vulnerability. Objective: The case of rural health vulnerability in South Africa is discussed to show that classifying people into vulnerable groups does not portray the complexity and intricacies of what it means to have vulnerability. We also wish to show that there are different kinds of vulnerabilities, and the difference between access vulnerability and illness vulnerability is highlighted. Methods: As part of a larger study, this case study is presented to show how vulnerability in a poor rural community in South Africa has to be understood in a contextual and dynamic manner as opposed to a static manner. Results: Family and social dynamics can influence health. For example, fractured families were seen as a vulnerable issue within the community, while being a person with a disability can lead to isolation and callous attitudes towards them. It is these family and social dynamics that lead proximally to vulnerability to ill health. Conclusions: A contextual approach can assist in giving a more layered understanding of vulnerability than a checklist approach can do. Interventions to change health cannot be addressed simply by medical means. Social conditions need to be changed, and part of changing social conditions is the process of assisting those who are isolated or experience themselves as vulnerable to reconnect with others in the community. Poverty leads to social exclusion; social and family inclusion may be key to well-being.